2021
DOI: 10.1007/s00223-020-00793-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined Biomaterials: Amniotic Membrane and Adipose Tissue to Restore Injured Bone as Promoter of Calcification in Bone Regeneration: Preclinical Model

Abstract: Discarded tissues, like human amniotic membranes and adipose tissue, were investigated for the application of Decellularized Human Amniotic Membrane (DAM) as a viable scaffold for transplantation of Adipose-derived stromal cells (ASCs) in bone regeneration of non-healing calvarial defects in rats. Amniotic membrane was decellularized to provide a scaffold for male Wistar rats ASCs expansion and transplantation. ASCs osteoinduction in vitro promoted the deposition of a mineralized bone-like matrix by ASCs, as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…As an interfacial matrix between old and new bone, the presence of the reversal line demarcated the pattern of bone deposition in the furcation defect and demonstrated the osteoconduction of the amniotic membrane collagenous matrix. The collagenous niches for osteogenesis were confirmed between the DAM folds and between loose collagenous fibers of the DAM, as observed previously in multilayered DAM [32].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As an interfacial matrix between old and new bone, the presence of the reversal line demarcated the pattern of bone deposition in the furcation defect and demonstrated the osteoconduction of the amniotic membrane collagenous matrix. The collagenous niches for osteogenesis were confirmed between the DAM folds and between loose collagenous fibers of the DAM, as observed previously in multilayered DAM [32].…”
Section: Discussionsupporting
confidence: 83%
“…DAM has been investigated in vivo for guided bone regeneration [ 28 ], assessing different amniotic membrane preservation methods [ 29 ]. The association of DAM with different cell sources has been examined in bone defects with periodontal ligament cells [ 30 ], osteoblasts [ 31 ], and ASCs [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…No statistical difference between AM and seeded AM was evidenced in this study. Dziedzic et al showed a significant higher bone formation using seeded AM compared the defect left empty (Dziedzic et al, 2021 ). However, they also failed to evidence significant difference between AM and seeded AM in contrast with the study of Semyari et al which observed an earlier bone regeneration when rabbit ADSCs-seeded AM was implanted in a rabbit calvarial bone defect (Semyari et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the included studies pointed that AM is mainly applied as a single layer. Few studies suggested to create a multilayered AM (Li et al, 2015 ; Dziedzic et al, 2021 ). This might enhance its thickness that initially ranges from 0.02 to 0.5 mm (Bourne, 1962 ).…”
Section: Discussionmentioning
confidence: 99%
“…Discarded tissues like amniotic membrane are easier to obtain than periosteum ECM. [ 67 ] Amniotic membrane is the innermost layer of the placenta, and it contains angiogenic growth factors, cytokines, and other active substances. Ghanmi et al.…”
Section: Different Materials For Constructing Tep Scaffoldsmentioning
confidence: 99%